Evaluation of Teacher Professional Development and Policy in the Digital Era - Zulfadmi; Muzakkir; Fahmi Hanifa (CV Naskah Aceh, 2024)
Digital transformation in the world of education requires teachers to continue to develop their professional competencies in order to meet the needs of 21st century learning. This study aims to evaluate the effectiveness of teacher professional development policies in the digital era, with a focus on the implementation of technology-based training and its impact on improving teacher competencies. The method used is a literature review by analyzing various sources of literature related to teacher professional development strategies in the digital era. The results of the study indicate that effective strategies include technology training, collaboration with colleagues, and participation in professional discussions. Thus, teachers can improve their competencies and prepare students to face increasingly complex digital challenges. In addition, support from schools, government, and related institutions is very important in implementing this strategy. This study is expected to provide guidance for education policy makers and related parties to improve teacher professionalism in the digital era in order to achieve better educational goals.